Attack architecture: design beyond the built - Holst, David (My University, 2022)
Since the early 1900s, the oxygen levels in the Baltic sea have been decreasing in the deep-water basins due to nutrients emitted from infrastructure, housing and farming. The result is a rapid increase of algae blooms in the surface water, suffocating the sediments in a process called “Hypoxia”. This leads to the Baltic Sea dying at a pace faster than ever before. The dead zones of the ocean are now reproducing by themselves and our efforts of reducing the pollution is no longer sufficient to reverse the trend. Through studies of up to date research and similar structures, this master thesis shows a design proposal working proactively with the issue. By breaking the layers in the brackish water with wind driven pumps, the oxygenated top layer of water can be relocated to the suffocated bottoms, activating the sediment and giving nature a chance to break down the algae and eventually heal itself. This project shows an example of how it is possible to revive the anoxic deep water basins, making it possible for sealife to strengthen and enable a cultural coastal life in the future. This is done through the design of an “off grid” research station in the Baltic sea’s extreme environment, designed with regenerative architecture in mind, focusing on sustainable periodic living with zero impact on nature as well as human well being in an isolated environment. The design is based on an understanding of the site with the aim of showing how architectural design can be used to push sustainable inventions further.
Keywords: Baltic Sea, Hypoxia, Oxygenation, Regenerative architecture, Flexibility, Invention